Training And Assistance To Improve Management Of Rumah Tahfiz Managers - Wahidi, Ridhoul; Nasrullah, Nasrullah; Amaruddin, Amaruddin; Syafril, Syafril; Khairuddin, Fiddian; Murni, Dewi (Jurnal Masyarakat Mengabdi, 2024)
The problem behind this PkM is the presence of rumah tahfiz which are scattered in almost all educational institutions, both formal and non-formal. Its presence requires proper management in order to produce good output. The aim of PkM is to provide knowledge about managerial management of the rumah tahfiz. The method applied through three stages, socialization, training and mentoring, and monitoring and evaluation. The location of the rumah tahfiz PkM activity is in Bente Village, Mandah District, Indragiri Hilir Regency, Riau. The results of activities regarding training and mentoring for the management of the rumah tahfiz can increase knowledge about the management of the rumah tahfiz for its managers starting from the Management of rumah tahfiz management both from a theoretical and practical aspect.